2008
DOI: 10.1111/j.1463-6409.2007.00320.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny of rootworms and related galerucine beetles (Coleoptera: Chrysomelidae)

Abstract: Molecular phylogeny of rootworms and related galerucine beetles (Coleoptera: Chrysomelidae). -Zoologica Scripta, 37 , The Galerucinae (Coleoptera: Chrysomelidae) sensu stricto (true galerucines) comprise a large assemblage of diverse phytophagous beetles containing over 5000 described species. Together with their sister taxon, the flea beetles, which differ from true galerucines by having the hind femora usually modified for jumping, the Galerucinae sensu lato comprises over 13 000 described species and is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
33
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 59 publications
2
33
0
4
Order By: Relevance
“…They suggested that more independent characters are needed. More recently, Gillespie et al [1] claimed to have the most comprehensive phylogeny estimation and showed consistency with previous molecular phylogenetic reconstruction of Galerucinae, but at the same time agreed that there was a lack of taxon representation from the Old World. There is no doubt that more characteristics need to be utilised from a more complete range of taxa selected from the Old and New Worlds, that is, better taxon sampling, including secondary sexual characteristics.…”
Section: Introductionsupporting
confidence: 51%
See 3 more Smart Citations
“…They suggested that more independent characters are needed. More recently, Gillespie et al [1] claimed to have the most comprehensive phylogeny estimation and showed consistency with previous molecular phylogenetic reconstruction of Galerucinae, but at the same time agreed that there was a lack of taxon representation from the Old World. There is no doubt that more characteristics need to be utilised from a more complete range of taxa selected from the Old and New Worlds, that is, better taxon sampling, including secondary sexual characteristics.…”
Section: Introductionsupporting
confidence: 51%
“…The present paper has three objectives: (1) to compile all known of SSCs found in chrysomelid beetles of the subfamily Galerucinae (sensu stricto) from all over the world, (2) to provide some explanation on functions of the various modified structures, and (3) to highlight the myriad forms of SSCs in the Galerucinae and their taxonomic significance in the Chrysomelidae.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…São aceitas, atualmente, 11 subfamílias, a saber: Bruchinae, Chrysomelinae, Criocerinae, Cryptocephalinae (incluindo Clytrinae e Chlamisinae), Donaciinae, Eumolpinae (incluindo Megascelidinae e Synetinae), Galerucinae (incluindo Alticinae), Cassidinae (incluindo Hispinae), Lamprosomatinae (incluindo Sphaerocharitinae), Sagrinae (Borowiec 1995;Lawrence & Newton 1995;Reid 1995;Staines 2002) e Spylopirinae (Reid 2000;Gómez-Zurita et al 2008) da história evolutiva desses táxons está longe de ser trivial (Kim et al 2003). Apesar de existirem estudos que suportem o conceito de duas subfamílias reciprocamente mono léticas (ver, por exemplo, Farrell 1998;Farrell & Sequeira 2004;Gillespie et al 2004;Gómez-Zurita et al 2008), estudos com amostragem mais abrangente indicam que a hipótese mais prevalente seja a de Alticinae poli lética, composta de uma série de linhagens incluídas em diversos níveis em Galerucinae (Lingafelter & Konstantinov 1999;Kim et al 2003;Gillespie et al 2003;Duckett et al 2004;Bünnige et al 2008;Gillespie et al 2008;Ge et al 2011Ge et al , 2012. Além da hipótese de Alticinae incluída em Galerucinae, a classi cação adotada aqui para os níveis abaixo de subfamília segue o sistema de Seeno & Wilcox (1982).…”
Section: Introductionunclassified